ECG descriptors of ventricular repolarization are associated with cardiac events in a gene-specific manner in long QT syndrome patients. (19th May 2022) - Morgat, C; Denjoy, I; Fressart, V; Badilini, F; Vaglio, M; Messali, A; Maison-Blanche, P; Leenhardt, A; Extramiana, F
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Assistance Publiques Hôpitaux de Paris (APHP) Background: Congenital long QT syndrome (LQTS) is still associated with syncope and a risk of sudden cardiac death despite the dramatic reduction in mortality associated with beta-blocker therapy. Current risk stratification tools are imperfect. Objective: To assess the contribution of automated scalar ECG descriptors of ventricular repolarization for arrrhythmic risk stratification in genotyped LQTS patients. Methods: Patients with genotyped type 1, 2 or 3 LQTS with at least 1 digital ECG recording have been included in the study. History at diagnosis, and follow-up data were collected. Cardiac events included syncope, aborted cardiac arrest, appropriate implantable cardioverter‐defibrillator therapy in VF zone, and sudden death. ECG were analyzed using the BRAVO algorithm embedded in the CalECG software, version 4.1.0. QT interval duration was manually checked but ECG descriptors of Ventricular Repolarization were fully automatic. Multivariate cox regression analysis were performed to identify parameters associated with cardiac events. Results: 467 patients (58% female, median age at diagnosis=25, LQT1, 2, 3 54%, 39%, 7%) were followed-up during 15.2±9.2 years. Rate of cardiac event was 1.2/100 patients-year before diagnosis and 0.9/100 patients-year during follow-up. QTc duration was associated with the occurrence of cardiac events in the whole study population (HR=1.01 95%CI 1.0-1.01, p=0.03). Ventricular repolarization parameters associated with cardiac events were different according to LQTS type. Cardiac events were associated with increased time to accumulate 50% of T-wave energy (HR=1.53 95%CI 1.04-2.26, p=0.03) in LQT1 but with a decrease in T-wave slopes (ascending slope HR=0.63 95%CI 0.17-0.75, p<0.01) in type 2 LQTS patients. QTc duration was not independently associated with cardiac events in genotype specific multivariate models. Conclusions: T-wave morphology parameters are associated with cardiac events in a gene-specific manner. Change in T-wave symmetry and T-wave flattening are associated with cardiac events in type 1 and type 2 LQTS respectively. The descriptors of ventricular repolarization are promising parameters or risk stratification beyond QTc duration in LQTS patients.